Controlled functionalization of carbon nanotubes by a solvent-free multicomponent approach - Paiva, M. C. (2010)
The present work reports the solvent-free, one-pot functionalization of multiwall carbon nanotubes (CNTs) based on the 1,3-dipolar cycloaddition of azomethine ylides using N-benzyloxycarbonyl glycine and formaldehyde. The surface morphology of the functionalized CNTs was investigated by scanning tunneling microscopy. The effect of temperature on the reaction was studied by thermogravimetry and X-ray photoelectron spectroscopy (XPS). XPS was a key technique for the detailed chemical analysis of the CNT surface. The formation of two major reaction products was observed, namely a cyclic benzyl carbamate and a pyrrolidine. The concentration of the two products varied with reaction temperature and time. At 180 °C, the main product was the cyclic benzyl carbamate, while at 250 °C the major product was the pyrrolidine. This simple, solvent-free chemical procedure yields CNTs with fine-tuned surface functionality.